2016
DOI: 10.1186/s13104-016-2191-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with intestinal parasitic infections among inmates of Kisii prison, Kisii county, Kenya

Abstract: BackgroundIntestinal parasitic infections are a major health problem worldwide. In Kenya intestinal parasitic infections are highly prevalent especially in prisons due to poor and/or inadequate infrastructure. The aim of this study was to establish the risk factors associated with intestinal parasites infection among inmates of Kisii prison, Kisii county, Kenya.MethodsFresh stool samples of 384 inmates in Kisii prison aged 20 years and above, were screened for intestinal parasitic infections between February a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 11 publications
3
18
3
Order By: Relevance
“…Accordingly, 42.6% of the participants were infected with at least one intestinal parasite species. The prevalence in the present study is lower than other studies conducted in Ethiopia and other prisons in Africa [17, 20, 21], but higher compared to a study conducted among inmates of Kisii prison, Kenya with prevalence of 24.7% [22]. On the other hand, the prevalence in this study is comparable with the report from Omdurman prison, Sudan, which revealed an overall prevalence of 49% [23].…”
Section: Discussionsupporting
confidence: 49%
“…Accordingly, 42.6% of the participants were infected with at least one intestinal parasite species. The prevalence in the present study is lower than other studies conducted in Ethiopia and other prisons in Africa [17, 20, 21], but higher compared to a study conducted among inmates of Kisii prison, Kenya with prevalence of 24.7% [22]. On the other hand, the prevalence in this study is comparable with the report from Omdurman prison, Sudan, which revealed an overall prevalence of 49% [23].…”
Section: Discussionsupporting
confidence: 49%
“…Hands can carry parasites that lead to infection and/or reinfection mainly in children who tend to present rudimentary hygienicsanitary habits [7,18,32]. Thus, regular hand washing is a well-defined protective factor for intestinal parasitic infections [33].…”
Section: Discussionmentioning
confidence: 99%
“…The amyloid amoebiasis was 66.8%, while the Giardia parasite was 36.8%. All these statistics carried out in Karbala city differed from the study conducted in Brazil (Rop et al, 2016). While studies agree with Natta C research, including (Abu-Madi et al, 2011) analysis, it con irmed that the highest prevalence of intestinal parasites in western Ethiopia was the giardia parasite at 13.3%.…”
Section: Figure 1: Graphical Columns Of Diseases During the Schoolyearsmentioning
confidence: 62%